(untitled) - Mountjoy, Alan B. (London, 1966)
The volume of relevant research and literature on this topic is growing but originates mainly from economists, sociologists, and political scientists; geographers have been slow to make contributions. One reason may be that geographers have been preoccupied with differentiation within the geography of production whereas this new field directs attention to the geography of consumption and a study of economies. This book aims to focus attention on the complex and inter-related problems--social, economic, political, and geographical--that come with development, placing particular emphasis on the problems which accompany attempts at industrialization. Focusing on the complex and interrelated social, economic, political, and geographic problems that attend under-development, this book presents one of the first contributions from a geographer on what has been called the most important economic problem of the modern world.
Keywords: Chính sách công nghiệp,Industrial policy